Cabinets of Curiosities - Petrillo, Connie (Connie Petrillo, 2012)
In Australia they have recently set up protocols for working with children in art. This will raise spectres and challenging issues for artists and art in general. The depiction of children may become a thing of the past and completely forbidden within our lifetimes and hence this portion of the humanity of art will be lost forever. Representation of children will become 'cabinets of curiosities'.